Perspektif Hukum Ekonomi Syari’ah Tentang Perjanjian Upah Borongan Pembangunan - Syaripudin, Enceng Iip; Nurlailawati, Siti (STAI Al-Musaddadiyah Garut, 2025)
This study aims to analyze the perspective of sharia economic law on the practice of wholesale wage agreements in development, especially in the Tilawatil Quran Development Institute (LPTQ) of Garut Regency. The practice of wholesale wage agreements is a phenomenon that is still quite common in the community, but there has been no in-depth study of its conformity with the principles of sharia economic law. The research method used is a case study with a qualitative approach. Data collection was conducted through interviews, observations, and documentation studies. Primary data are obtained from parties involved in the practice of piecemeal agreements in LPTQ Garut, while secondary data comes from literature related to shari'ah economic law. The results of the study show that the practice of wholesale wage agreements for development at LPTQ Garut in general is in accordance with the principles of sharia economic law. The wages provided are considered fair and proportional based on mutual agreement. However, there are several aspects that need attention, such as ensuring work safety, paying wages on time, and transparency of information between the parties involved. Based on the analysis of maqashid shari'ah (the purpose of Islamic law), the practice of wholesale wage agreements in LPTQ Garut can provide maslahah (benefit) for the parties involved. However, efforts are needed to strengthen aspects of sharia compliance in order to create more comprehensive justice, balance, and benefit. Keywords: Shari'ah Economics, Wage Agreement, Volume, Development